Emerging ideas. Transnational family dynamics during the COVID-19 pandemic: A scoping review - Végh, J.; Voicu, B.; Barroso, M. M.; Deliu, A.; Heiman, T.; Hossu, I.-E.; Karpava, S.; Maxhelaku, A.; Olenik-Shemesh, D.; Ślusarczyk, M.; Wilsch, M.; Wojtyńska, A.; et al. (Family Relations, 2025)
Objective The article reviews literature on the implications and effects of the COVID-19 pandemic on transnational families (TNFs), gathering up-to-date evidence of how the pandemic changed the dynamics of TNFs in different life dimensions, how these families have coped with adversity, and how the academic debate is recognizing the complexity of transnationality in situations of crisis. Background Transnational families consist of members who live in multiple countries while maintaining a sense of familyhood (Bryceson & Vuorela, 2002). The COVID-19 pandemic presents significant challenges for TNFs as crisis responses prioritize national borders and institutions. Method A scoping review was conducted using Arksey and O'Malley's (2005) framework, the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) extension for Scoping Reviews (Tricco et al., 2018), and Peters et al.'s (2015) guidance for systematic reviews. Of the 113 references identified, 29 met the scoping review's inclusion criteria. Results The effects of the pandemic on TNFs were particularly noticeable in terms of uncertainty, psychological health, communication, social networks, care, and time use. Conclusion Mobility restrictions and concerns about disease spread were significantly challenging. Although TNFs were able to adapt rapidly by using technology and innovative solutions to maintain their relationships, social inequalities were also exposed by the pandemic. Implications Robust support systems are needed for TNFs, both at their point of origin and destination, to assist them in managing challenging circumstances that disrupt their daily routines and interactions. Future research could further explore and develop these support systems to better address these challenges. s to better address these challenges.